Discovering electronic music [videorecording] - Wilets, Bernard ([S.l. s.n.], 1983)
Portrays the physical basic of music and how music can be created and altered by electronic means. Demonstrates digital sound synthesizer and use of computer terminals to display, control, and change musical compositions.
VHS.
Keywords: Electronic music; Musical instruments, Electronic